Outcomes and lessons learnt from practice ofretrograde intrarenal surgery (rirs) in a paediatricsetting of various age groups: a global study across 8 centres - ŞEKERCİ, ÇAĞRI AKIN; TANIDIR, YILÖREN (My University, 2022)
INTRODUCTION AND OBJECTIVE: We aim to analyse and report the practice, outcomes and lessons learnt from a global series of retrograde intrarenal surgery (RIRS) in a paediatric multicentre series. METHODS: Retrospective review of anonymised pooled data gathered globally from 8 centres in paediatric patients ( 18 years of age) who had renal stones and underwent RIRS from 2015 to 2020 was performed. Patient demographics, perioperative parameters, stone characteristics, complications and stone-free rate (SFR) were analysed. Residual fragments(RFs) were defined as a single fragment >2mm or multiple fragments. Our cohort was stratified by age into 3 groups : 5 years (Group A), 5-10 years (Group B) and 10 years (Group C). T-test and ManneWhitney were used for continuous variables. Categorical data between groups were analysed using the c2 test. RESULTS: 314 patients were included for analysis. Mean age was 9.54 þ/- 4.76 years. The number of patients in groups A, B and C were 67 (21.3%), 83 (26.4%) and 164 (52.2%) respectively. The mean stone size was 10.7 þ/- 4.62 mm. While pre-stenting was performed in 155 (49.4%) of patients, ureteral access sheaths (UAS) was used in 54.5% of patients, and majority (71%) utilizing holmium laser for stone fragmentation. The SFR was 75.5% with 77(24.5%) having residual fragments. All post-surgical complications were minor Clavein Dindo (CD) classification and included ureteric injury (n[5), pelvicalyceal injury (n[5, all in group A), fever (n[20), hematuria (n [11) and sepsis (n[2). CONCLUSIONS: RIRS is acceptable as a firstline intervention in the paediatric population with reasonable efficacy and low morbidity; Complications are slightly higher in Group A and this should be taken into account while counselling patients.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Üroloji; Pediatrik Üroloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Urology; Pediatric Urology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; SURGERY; Cerrahi; Nefroloji; Surgery; Nephrology